Analysis of activation energy in magnetohydrodynamic flow with chemical reaction and second order momentum slip model. (September 2018) - Majeed, Aaqib; Noori, F.M.; Zeeshan, A.; Mahmood, T.; Rehman, S.U.; Khan, I.
Abstract: This paper is communicated theoretically to study the collective effects of Arrhenius activation energy and binary chemically reactive species in the presence of the second order momentum slip model which has not been studied so far. To support these declaration in addition with electrically conducting boundary layer flow and heat transport have considered towards an exponential stretching sheet. The current study incorporates the impact of activation energy, temperature difference ratio parameter, 1st and 2nd order slip parameter, chemical reaction rate on fluid velocity, fluid temperature and concentration of chemical species are elaborated through graphically and discussed in detail. Appropriate transformations are betrothed to acquire nonlinear highly coupled ordinary differential equations (ODE's) from partial differential equations which are then solved numerically by employing finite difference collocation process that apply three-stage Lobatto IIIa scheme. The obtained results confirm that an excellent agreement is achieved with those available in open literature. It is found that concentration profile decreases in the presence of chemical reaction rate and temperature difference ratio parameter whereas opposite demeanour is seen for activation energy.